Hospital volunteering experiences suggest that new policies are needed to promote their integration in daily care: Findings from a qualitative study - Gonella Silvia; Canzan Federica; Larghero Enrico; Ambrosi Elisa; Palese Alvisa; Dimonte Valerio (Sciendo, 2019)
To explore Hospital Volunteers' (HVs) motivations and experiences, as well as the strategies they adopt to overcome challenging situations during volunteering and the needs they perceive.